Chemical constituents from the twigs and leaves of Lyonia ovalifolia. (June 2018) - Zhao, De-Rui; Su, Li-Hua; Li, Rong-Tao; Chen, Xuan-Qin; Li, Hong-Mei
Abstract: Phytochemical investigation on the twigs and leaves of Lyonia ovalifolia led to the isolation of thirty-four compounds, including six grayanane diterpenoids (1–6 ), sixteen ursane triterpenoids and their glycosides (7–22 ), and twelve phenolic components (23–34 ). This study is the first report of compounds1, 4, 5 and7 –34 in L. ovalifolia, while compounds1, 4, 5, 7 –28 and30 –34 have not been recorded in the genus Lyonia previously. The structures of these compounds were elucidated using spectroscopic methods and by comparing their data to those reported in the literatures. The anti-HIV-1 and anti-influenza virus activities of compounds1 –7, 10 –14, 16, 18 –22, 24, 25, 30 –34 were also evaluated. The chemotaxonomic significance of the isolates has been discussed. Highlights: Thirty-four compounds, including diterpenoids, triterpenoids and phenolic components were isolated from Lyonia ovalifolia . This is the first report of compounds1, 4, 5 and7 –34 in L. ovalifolia, and compounds1, 4, 5, 7 –28 and30 –34 in Lyonia . The chemotaxonomic significance of the isolates has been discussed.